Conversor SEPIC empregando um snubber regenerativo associado a um regulador linear de corrente para acionar e controlar LEDs de potência - Burgardt, Ismael (2015)
This paper presents a universal-input AC electronic lighting system using a non-isolated SEPIC PFC rectifier to drive and control power LEDs currents. One energy regenerative snubber for reducing the converter switching losses and improve the system efficiency is proposed. The dimmable flicker-free current in the LEDs array is obtained through a linear current regulator placed in the SEPIC’s output terminals. In order to reduce the efficiency impairment, the conditions for achieving minimum energy loss in the current regulator are also detailed. Point of minimum energy loss in the linear regulator is adjusted through valley detector circuit in closed loop system operation. The operation stages as well as the theoretical waveforms and main equations at steady state of the proposed SEPIC rectifier using the regenerative snubber are described. To verify the theoretical analysis carried out, experimental results of two prototypes (42 W and 145 W) operating from 90 to 240 V and output power from 15 to 100% for 35 LEDs are also presented.